2021
DOI: 10.1002/adom.202101784
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Exciton Annihilation Effects in Thermally Activated Delayed Fluorescence Materials

Abstract: Important parameters for the design and performance of thermally activated delayed fluorescence (TADF) emitters are the forward and reverse intersystem crossing rates between singlet and triplet states. The magnitude of these rates is determined from the prompt and delayed transient photoluminescence decay. It is demonstrated that this photoluminescence decay strongly depends on the initial photoexcited population density due to exciton–exciton annihilation processes. By kinetic modeling of the power‐dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Moreover, it corresponds very well to the k TTA of 8 × 10 −18 m 3 s −1 found in our recent TrPL study on CzDBA. [27] Surprisingly, we find that a single k TTA value fits the entire investigated temperature range (295-215 K). Recently, a kinetic Monte Carlo study of TTA in conjugated organic semiconductors found that the temperature dependence of TTA is weak in our investigated temperature range, given that the energetic disorder is small.…”
Section: Photophysical Parametersmentioning
confidence: 63%
See 4 more Smart Citations
“…Moreover, it corresponds very well to the k TTA of 8 × 10 −18 m 3 s −1 found in our recent TrPL study on CzDBA. [27] Surprisingly, we find that a single k TTA value fits the entire investigated temperature range (295-215 K). Recently, a kinetic Monte Carlo study of TTA in conjugated organic semiconductors found that the temperature dependence of TTA is weak in our investigated temperature range, given that the energetic disorder is small.…”
Section: Photophysical Parametersmentioning
confidence: 63%
“…We note that the role of SSA is controversial, either being considered a significant contribution to the roll-off, [41][42][43] whereas other works deem SSA unimportant, [20,37] making it necessary to consider its significance in this study. In our recent TrPL study on CzDBA neat films we found that SSA was not a major decay process, [27] which justifies neglecting it in our OLED analysis. Turning our attention to SPQ, the triplet density exceeds the singlet density often by more than an order of magnitude under steady state conditions, making TPQ a far more relevant process than SPQ.…”
Section: Effect Of Various Quenching Processes On the Efficiencymentioning
confidence: 77%
See 3 more Smart Citations